Russia's Sisters of Mercy and the Great War : more than binding men's wounds - Stoff, Laurie (Modern war studies., 2015)
They are war stories, filled with danger and deprivation, excitement and opportunity, sorrow and trauma, scandal and controversy-and because they are the war stories of nurses, they remain largely untold. Laurie Stoff's pioneering work brings the wartime experiences of Russia's ""Sisters of Mercy"" out of the shadows to show how these nurses of the Great War, far from merely binding wounds, provided vital services that put them squarely in traditionally ""masculine"" territory, both literally and figuratively. While Russian nursing shared many features of women's medical service in other nation.